Narrativas da ordem: gênero e sexualidade nas escolas cívico-militares - Silveira Almeida, Letícia (Universidade Federal de São Carlos, 2026)
This Undergraduate Thesis analyzes the implementation of civic-military schools in the public education system through the lens of gender and sexuality studies. The general objective is to understand how the civic-military model operates in regulating and controlling the bodies of dissident identities and the LGBTQIAPN+ community, as well as to investigate the links between political neoconservatism, militarism, and the production of hegemonic masculinities within the school space. Methodologically, this qualitative research articulates documentary and bibliographic methods, drawing its analytical corpus from the 2024 Supreme Federal Court Public Hearing speeches, the theoretical frameworks of Michel Foucault and Judith Butler, and the student conduct manuals from militarized institutions in the states of São Paulo, Mato Grosso, and Paraná. The results indicate that the analyzed model operates as a binary and punitive gender technology aimed at standardizing and homogenizing students through rigid disciplinary regimes. It is evident that such aesthetic and behavioral restrictions penalize diversity and foster the institutional silencing of plural subjectivities. The study concludes that the neoconservative alliance uses school militarization as a mechanism for moral and social containment, thereby undermining the democratic and emancipatory function of public schooling guaranteed by the 1988 Constitution.
Narratives of order: gender and sexuality in civic-military schools
Keywords: Escolas cívico-militares; Gênero; Sexualidade; Neoconservadorismo; Pedagogia militar; Civic military-schools; Gender; Sexuality; Neoconservadorism; Military pedagogy; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 5. Igualdade de Gênero